Calmodulin-binding proteins: A journey of 40 years. (November 2018) - Sharma, Rajendra K.; Parameswaran, Sreejit
Graphical abstract: Highlights: We summarized four decades of research work in the area of calmodulin-binding proteins. Discovery of high molecular weight calmodulin–binding protein, a calpastatin homolog. Discovery and purification of calcineurin. Elucidated the mechanism and importance of these proteins in normal and diseased conditions. Abstract: The proteins which bind to calmodulin in a Ca 2+ -dependent and reversible manner are known as calmodulin-binding proteins. These proteins are involved in a multitude of processes in which Ca 2+ and calmodulin play crucial roles. Our group elucidated the mechanism and importance of these proteins in normal and diseased conditions. Various calmodulin-binding proteins were discovered and purified from bovine tissue including a heat stable calmodulin-binding protein 70, calmodulin-dependent protein kinase VI and a high molecular weight calmodulin-binding protein (HMWCaMBP). We observed a complex interplay occurs between these and other Ca 2+ and calmodulin-binding proteins during cardiac ischemia and reperfusion. Purified cardiac HMWCaMBP is a homolog form of calpastatin and an inhibitor of the Ca 2+ -activated cysteine proteases, calpains and therefore can have cardioprotective role in ischemic conditions. Calcineurin is a Ca 2+ and calmodulin-dependent serine/threonine protein phosphatase showed increased phosphatase activity in ischemic heart through its direct interaction with Hsp70 and expression of calcineurin following ischemia suggests self-repair and favorable survival outcomes. Calcineurin was also found to be present in other tissues including the eye; where its expression and calcineurin phosphatase activity varied. In neurons, calcineurin may play a key role in initiating apoptosis-related pathways especially in epilepsy. In colorectal cancer we demonstrated high calcineurin phosphatase activity and simultaneous overexpression of calcineurin. The impact of calcineurin signaling on neuronal apoptosis in epilepsy and its use as a diagnostic marker for colorectal cancer requires in-depth study.